Phosphorylation of ZEN-4/MKLP1 by Aurora B regulates completion of cytokinesis - Guse, Annika; Mishima, Masanori; Glotzer, Michael (Current biology, 2005)
Summary The central spindle regulates the formation and positioning of the contractile ring and is essential for completion of cytokinesis [1]. Central spindle assembly begins in early anaphase with the bundling of overlapping, antiparallel, nonkinetochore microtubules [2, 3], and these bundles become compacted and mature into the midbody. Prominent components of the central spindle include aurora B kinase and centralspindlin, a complex containing a Kinesin-6 protein (ZEN-4/MKLP1) and a Rho family GAP (CYK-4/MgcRacGAP) that is essential for central spindle assembly [4]. Centralspindlin localization depends on aurora B kinase [5]. Aurora B concentrates in the midbody and persists between daughter cells. Here, we show that in C. elegans embryos and in cultured human cells, respectively, ZEN-4 and MKLP1 are phosphorylated by aurora B in vitro and in vivo on conserved C-terminal serine residues. In C. elegans embryos, a nonphosphorylatable mutant of ZEN-4 localizes properly but does not efficiently support completion of cytokinesis. In mammalian cells, an inhibitor of aurora kinase acutely attenuates phosphorylation of MKLP1. Inhibition of aurora B in late anaphase causes cytokinesis defects without disrupting the central spindle. These data indicate a conserved role for aurora-B-mediated phosphorylation of ZEN-4/MKLP1 in the completion of cytokinesis.